Clinical and demographic profile of chromoblastomycosis in a referral service in the midwest of São Paulo state (Brazil) - Marques, Gabriela Franco; Barreto, Jaison Antônio; Masuda, Paula Yoshiko; Wachholz, Patrick Alexander [UNESP]; Sousa, Juliana Martins Prazeres (FapUNIFESP (SciELO), 2015)
Chromoblastomycosis is one of the most frequent deep mycoses found in rural populations. This cross-sectional, retrospective and descriptive study was conducted with cases of chromoblastomycosis diagnosed throughout 20 years. A higher prevalence was observed among White male rural workers, with an average age of 59.69 years. Median time between onset of symptoms and diagnosis was 156 months. Lesions were predominantly located on the lower limbs; 34% of cases reported previous trauma. The most common associated symptoms were itching, pain and burning sensation. Mycological examination was positive in 91% of cases and Fonsecaea pedrosoi was the most prevalent etiologic agent.
Keywords: Chromoblastomycosis; Epidemiology; Fungi; Mycoses